A Quantitative Comparative Analysis of NASA-TLX Workload between Staff and Non-Staff Employees in a Pharmaceutical Manufacturing Organization: Implications for Knowledge Management - Rian Bimo Ankhal; Muharman Lubis; Hanif Fakhrurroja; Muhammad Fakhrul Safitra (Scientific Journal of Informatics, 2026)
Purpose: In pharmaceutical production, personnel may be exposed to different workload situations, since their job functions are affected by strict operational and regulatory standards. Non-personnel workers and personnel workers have different duties which can affect their perception of workload and their participation in knowledge sharing activities. However, empirical evaluations of the workload characteristics of these employee cohorts by means of the NASA Task Load Index (NASA-TLX) are still scarce. This study explores the perceived workload attributes of staff and non-staff workers on six modified NASA-TLX scales. The implications of the identified trends for knowledge management strategies are discussed. Methods: The method used for this research was quantitative, comparative and cross-sectional. The study’s data were collected using a structured questionnaire. The sample selected for the study was 30 staff and non-staff members of a pharmaceutical manufacturing company using purposive sampling. The tool assessed six modified NASA-TLX workload factors; Mental Demand, Physical Demand, Temporal Demand, Performance, Effort and Frustration Level using a five-point Likert scale. Dimension total Pearson correlation analysis and Cronbach’s alpha reliability test were performed to assess the instrument with the same data set. Descriptive analyses of the workload characteristics of staff and non-staff personnel were conducted using group mean scores and mean differences. No assertions regarding statistical significance were provided. Result: Non-staff personnel had higher mean scores than staff personnel in Mental Demand, Physical Demand, Temporal Demand, Effort and Frustration Level. For workload, the largest mean differences were found in Temporal Demand and Effort. Non-staff personnel also reported a higher Performance score. The Performance items, however, are positively worded and imply that higher scores reflect a more positive view of work accomplishment and quality, not a greater workload. The patterns shown here indicate that role-specific knowledge management practices can support continued improvement, learning and knowledge sharing activities. Novelty: This study presents the analysis of staff and non-staff employees according to their role and a complete workload analysis in the context of a pharmaceutical manufacturing environment with the modified NASA-TLX framework. The results provide a pragmatic basis for the development of knowledge management strategies relevant to the operational tasks and workload characteristics of each category of employees.